Poetry workshop (Journal of Parents and Teachers, 2023)
The article talks about the importance of the use of words and the magic that we can create through the poetry. It also includes some tips to employ the poetry in the classrooms in an effective way mixing it with other assignments as arts, music or corporal expression.
Keywords: poetry; education; arts